Do Women With Atrial Fibrillation Experience More Severe Strokes?: Results From the Austrian Stroke Unit Registry. Issue 3 (March 2017) - Lang, Clemens; Seyfang, Leonhard; Ferrari, Julia; Gattringer, Thomas; Greisenegger, Stefan; Willeit, Karin; Toell, Thomas; Krebs, Stefan; Brainin, Michael; Kiechl, Stefan; Willeit, Johann; Lang, Wilfried; et al.
Abstract : Background and Purpose—: Ischemic strokes associated with atrial fibrillation (AF) are more severe than those of other cause. We aim to study potential sex effects in this context. Methods—: In this cross-sectional study, 74 425 adults with acute ischemic stroke from the Austrian Stroke Unit Registry were included between March 2003 and January 2016. In 63 563 patients, data on the National Institutes of Health Stroke Scale on admission to the stroke unit, presence of AF, vascular risk factors, and comorbidities were complete. Analysis was done by a multivariate regression model. Results—: Stroke severity in general increased with age. AF-related strokes were more severe than strokes of other causes. Sex-related differences in stroke severity were only seen in stroke patients with AF. Median (Q25, 75 ) National Institutes of Health Stroke Scale score points were 9 (4, 17) in women and 6 (3, 13) in men ( P <0.001). The interaction between AF and sex on stroke severity was independent of age, previous functional status, vascular risk factors, and vascular comorbidities and remained significant in various subgroups. Conclusions—: Women with AF do not only have an increased risk of stroke when compared with men but also experience more severe strokes. Abstract : Supplemental Digital Content is available in the text.